The Impact of the Digital Economy on Carbon Emissions using the STIRPAT Model - Karaki, Bassam Abu; Al_kasasbeh, Omar; Alassuli, Abdalla; Alzghoul, Amro (International Journal of Energy Economics and Policy, 2023)
As a new economic factor, digitalization plays a vital role in society, economy, and the environment. Based on the expanded STIRPAT model, this paper empirically tests the impact of digital economy on carbon emissions by panel data from 2011 to 2021 in BRICS countries. Utilizing a variety of econometric techniques, the study’s objectives were met. For instance, unit root properties are investigated using the CIPS and CADF techniques, while cointegration is examined using the panel cointegration approach of Westerlund and Edgerton (2008). The findings demonstrate the existence of a long-term correlation between carbon emissions, population, GDP, technical level, and digital economy. We propose that governments must not only implement hedging policies to reduce Carbon emissions caused by the digital economy at an early stage but also promote the development of the digital economy in order to accomplish the objective of global collaborative environmental protection.